2006
DOI: 10.1007/s10071-006-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Movement characteristics support a role for dead reckoning in organizing exploratory behavior

Abstract: Rat exploration is an organized series of trips. Each exploratory trip involves an outward tour from the refuge followed by a return to the refuge. A tour consists of a sequence of progressions with variable direction and speed concatenated by stops, whereas the return consists of a single direct progression. We have argued that processing self-movement information generated on the tour allows a rat to plot the return to the refuge. This claim has been supported by observing consistent differences between tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…As in the recording experiment, animals were trained and tested under both standard (with a prominent visual cue) and dark conditions; these conditions were maintained over the entire duration of each training or testing session. As reported previously [34,36] animals were less accurate at homing under dark conditions compared to light conditions (ANOVA, main effect of condition; homing error: F 1,540 = 11.224, p = 0.0009; homing circuity: F 1,539 = 31.463, p < 10 −7 ). During optogenetic testing, NPH→DTN photoinhibition (on a 10 sec on/1 sec off cycle throughout the entire session) did not affect animals' ability to accurately direct their homing paths toward the refuge under standard, well-illuminated conditions, but impaired their homing in the absence of visual cues (Fig.…”
Section: Manipulation Of Homing Behavior Via Hd Cell Instabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…As in the recording experiment, animals were trained and tested under both standard (with a prominent visual cue) and dark conditions; these conditions were maintained over the entire duration of each training or testing session. As reported previously [34,36] animals were less accurate at homing under dark conditions compared to light conditions (ANOVA, main effect of condition; homing error: F 1,540 = 11.224, p = 0.0009; homing circuity: F 1,539 = 31.463, p < 10 −7 ). During optogenetic testing, NPH→DTN photoinhibition (on a 10 sec on/1 sec off cycle throughout the entire session) did not affect animals' ability to accurately direct their homing paths toward the refuge under standard, well-illuminated conditions, but impaired their homing in the absence of visual cues (Fig.…”
Section: Manipulation Of Homing Behavior Via Hd Cell Instabilitysupporting
confidence: 81%
“…6B), suggesting that the manipulation of the HD signal stability was selective to the angular component of their navigational response. Previous work in the food-carrying task has also shown that rats are able to modulate their homing path speeds as a function of the distance they must travel, such that the point of greatest velocity falls near the midpoint of their homing path [36]. We therefore performed a kinematic analysis on the rats' return trips to the refuge in order to assess their ability to perform linear distance estimation.…”
Section: Manipulation Of Homing Behavior Via Hd Cell Instabilitymentioning
confidence: 99%
“…These differences are well documented across taxa, including arachnids (Seyfarth and Barth 1972;Seyfarth et al 1982), hymenopterans Wehner 1988, 1994), decapods (Layne et al 2003a, b;Kamran and Moore 2015), and mammals (Etienne et al 1996;Etienne and Jeffery 2004;Wallace et al 2006). In particular, animals walk slowly and their paths are more sinuous on outbound journeys while inbound paths are fast, straight, and highly directed along an integrated homing vector.…”
Section: Discussionmentioning
confidence: 98%
“…On an open field, rats will make wandering excursions from a cued home base, after which they will return to the home base in a direct and rapid manner (Wallace et al, 2006). Over the course of an entire trial, rats may make several of these exploratory movements, each followed by a direct return trip.…”
Section: Direct Tripsmentioning
confidence: 99%
“…Direct trips, defined as distinctive rapid crossing of the table toward the cue location (Wallace et al, 2006), were also used as a behavioral measure. On an open field, rats will make wandering excursions from a cued home base, after which they will return to the home base in a direct and rapid manner (Wallace et al, 2006).…”
Section: Direct Tripsmentioning
confidence: 99%